Spatial variability of the productivity and the nutritional condition of coffee canephora - Fonseca, Abel Souza; Lima, Julião Soares de Souza; Silva, Samuel de Assis; Xavier, Alexandre Candido; Neto, Antonio Pereira Drumond (Coffee Science - ISSN 1984-3909, 2015)
Utilizing precision farming techniques along with the Diagnosis and Recommendation Integrated System (DRIS) allows crop management to be improved, thereby making it possible to better control plant nutrition and to assist in reducing fertilizer expenditures. This study aimed to evaluate the spatial variability of the nutritional status of conilon coffee (Coffea canephora), using the Nutritional Balance index (NBI). 140 points were georeferenced within a coffee crop, each sampling point contained five plants. Leaf samples were analyzed in order to determine levels of N, P, K, Ca, Mg, S, Fe, B, Zn, Mn and Cu. The crop showed itself to have a nutritional imbalance, as shown by the deficiency and excess variation of some nutrients in the crop. The nutritional balance index (NBI) was not correlated with productivity (Prod), indicating that, when the crop has a high nutritional imbalance IBN is not a good tool for establishing nutritional standards for conilon coffee.